2014
DOI: 10.1371/journal.pone.0095013
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant, Tissue Factor-Bearing Microparticles in Bronchoalveolar Lavage of Interstitial Lung Disease Patients: An Observational Study

Abstract: Coagulation factor Xa appears involved in the pathogenesis of pulmonary fibrosis. Through its interaction with protease activated receptor-1, this protease signals myofibroblast differentiation in lung fibroblasts. Although fibrogenic stimuli induce factor X synthesis by alveolar cells, the mechanisms of local posttranslational factor X activation are not fully understood. Cell-derived microparticles are submicron vesicles involved in different physiological processes, including blood coagulation; they potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 38 publications
2
40
0
Order By: Relevance
“…When patients were further divided into idiopathic pulmonary fibrosis (IPF) and non-IPF groups, the MP-TF procoagulant activity was significantly higher in the former group. Additionally, a statistically significant negative correlation was found between TF-bearing microparticles and both forced vital capacity and DLCO in IPF patients [49]. In the same study, in vitro assays showed that an oxidative stimulus, namely H 2 O 2 , increased the production of procoagulant microparticles by alveolar epithelial cells in culture [49].…”
Section: Diffuse Parenchymal Lung Diseasesmentioning
confidence: 79%
See 2 more Smart Citations
“…When patients were further divided into idiopathic pulmonary fibrosis (IPF) and non-IPF groups, the MP-TF procoagulant activity was significantly higher in the former group. Additionally, a statistically significant negative correlation was found between TF-bearing microparticles and both forced vital capacity and DLCO in IPF patients [49]. In the same study, in vitro assays showed that an oxidative stimulus, namely H 2 O 2 , increased the production of procoagulant microparticles by alveolar epithelial cells in culture [49].…”
Section: Diffuse Parenchymal Lung Diseasesmentioning
confidence: 79%
“…Additionally, a statistically significant negative correlation was found between TF-bearing microparticles and both forced vital capacity and DLCO in IPF patients [49]. In the same study, in vitro assays showed that an oxidative stimulus, namely H 2 O 2 , increased the production of procoagulant microparticles by alveolar epithelial cells in culture [49]. Local synthesis of coagulation factor X and its activation to factor Xa in the lung has been implicated in the pathogenesis of IPF.…”
Section: Diffuse Parenchymal Lung Diseasesmentioning
confidence: 88%
See 1 more Smart Citation
“…Mononuclears may generate pro-inflammatory MPs upon activation and apoptosis with a calcium-dependent and p38 mitogen-activated protein kinasedependent mechanisms resulting in impact of cytokines, bacterial products, P-selectin, histamine, catecholamines, angiotensin-II, cigarette smoking [36][37][38][39][40]. Furthermore, mononuclear cell-derived MPs may appear spontaneously beyond obvious cause in physiological state [39,40].…”
Section: Biological Role and Function Of Mpsmentioning
confidence: 99%
“…Plasma levels of MPs are altered in rheumatoid arthritis (2), oral cancer (3) and diabetes (4). Although the presence of MPs in saliva, urine, bronchoalveolar lavage and synovial fluid have already been shown (5,6), its detection in gingival crevicular fluid (GCF) still needs to be confirmed.…”
Section: Introductionmentioning
confidence: 99%